2019
DOI: 10.1080/02640414.2019.1681864
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of an Australian football small-sided game to assess kicking proficiency

Abstract: In Australian Football (AF), small sided games have been used extensively as an alternative training method for technical and physical adaptations. Considering their application to AF, it is surprising a valid and reliable small-sided game kicking assessment remains absent. Therefore, the aim of this study was to develop a valid and reliable 5v6 Australian football small-sided game kicking proficiency assessment. Youth male AF players (n = 145) from different stages within the AF talent pathway were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…In line with this method of assessment, the current results highlight the importance of an athlete’s in-game performance to being identified as talented. While researchers and associations still investigate the relationships between selection and non-selection on isolated physical and performance tests [ 10 , 15 , 43 ], there has been a recent shift in Australian Football to understand key in-game performance indicators influence on selection [ 11 , 13 , 14 ], coupled with the devleopment of more dynamic skill based assessments [ 46 , 47 ]. Findings have indicated that match performance outcomes, such as contested possessions and delivering the ball into the forward 50-metre area, differentiate players drafted and not-drafted [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this method of assessment, the current results highlight the importance of an athlete’s in-game performance to being identified as talented. While researchers and associations still investigate the relationships between selection and non-selection on isolated physical and performance tests [ 10 , 15 , 43 ], there has been a recent shift in Australian Football to understand key in-game performance indicators influence on selection [ 11 , 13 , 14 ], coupled with the devleopment of more dynamic skill based assessments [ 46 , 47 ]. Findings have indicated that match performance outcomes, such as contested possessions and delivering the ball into the forward 50-metre area, differentiate players drafted and not-drafted [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AF SSG developed by Bonney, Berry, Ball, and Larkin (2019c) was used in the current study. The game involved 11 players (six attacking and five defending) competing within the 50m arc (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the total score (summation of decision making and skill execution scores) significantly predicted disposal efficiency in competition performance (Piggott et al, 2019b). SSG's allow players greater opportunities to gain possession of the ball and display their skill level, as well as apply game strategy and tactics (Bonney et al, 2019b). The SSG test has a high level of representative task design as perceptual information that occurs in competition is presented to the participant and opportunity is provided to couple action to available perceptual information like the competition setting (Piggott et al, 2019c).…”
Section: Small-sided Gamesmentioning
confidence: 99%